Importance of vertigo classification in the emergency department and its effects on economic burden - Ekmekyapar, Muhammed; Ekmekyapar, Tuba; Gurbuz, Sukru (Annals of Medical Research, 2023)
Aim: Patients with vertigo present to the emergency department with their clinical status and social comfort significantly impaired. More importantly, diseases that can pose a life-threatening risk may also underlying vertigo. In our study, we aimed to detect life-threatening conditions in vertigo patients early, and to alleviate the economic burden by preventing unnecessary radiological imaging in emergency services.Materials and Methods: Three hundred eighteen patients were included in the study. The patients were divided into two groups as peripheral and central vertigo. Patients' age, sex, temperature, pulse, and arterial blood pressure values were examined. The complaints at admission were grouped as dizziness, dizziness+nausea-vomiting, and dizziness+neurological complaint. Furthermore, patients' examination findings, history of diseases, and laboratory data were recorded. Radiological imaging methods used in the emergency department, the requested consultations, peripheral-central vertigo, and hospitalization-discharge status were examined.Results: Of all patients, 287 (90.3%) and 31 (9.7%) had peripheral and central vertigo, respectively. The mean age of patients with peripheral vertigo was 52.34±17.38 years, while the mean age of patients with central vertigo was 68.06±19.56 years. There was a statistically significant difference between peripheral-central vertigo and age. A statistically significant difference was revealed between peripheral-central vertigo and systolic and diastolic blood pressure. In laboratory data, we found a significant difference between peripheral-central vertigo and glucose and CRP. Hypertension was the most common disease in the history.Conclusion: The etiology of vertigo should be clarified quickly and reliably in emergency departments. To this end, the patient's complaints and the findings obtained as a result of the examination along with auxiliary radiological imaging methods are vital. Thus, the diagnosis and treatment of patients with severe vertigo will be performed earlier, and unnecessary radiological imaging will be prevented. As a result, the economic burden will also decrease with the decrease in the examinations performed.
Keywords: Economic burden; Emergency department; Clinical features; Radiological imaging; Vertigo